Investigating the Effect of Leader Humility on Innovative Work Behavior: The Role of Civility Climate and Job Insecurity - Achmadi Achmadi; Hendryadi Hendryadi; Amelia Oktrivina; Donant Alananto Iskandar (Media Ekonomi dan Manajemen, 2023)
Humility is a leadership model inherent in Asian culture and is believed to impact employees' productive behavior and attitudes positively. By examining how leader humility affects the workplace's civility climate and innovative work behavior (IWB), the current study seeks to address the scarcity of studies on these relationships. We also posited that the perceived civility climate mediated the relationship between leader humility and IWB and examined the role of job insecurity as a boundary condition. PLS-SEM was applied to test hypotheses from data on 328 employees in various sectors in Jakarta. The analysis results indicate humility could promote perceived civility and innovative work behavior. In addition, we discovered that civility climate acted as a mediator in leader humility and IWB relationship. Moreover, we empirically reveal unique findings regarding the role of job insecurity as a moderator in the leader-humility-IWB and civility climate-IWB relationship. The present study is the first attempt to explore the role of intermediate civility climate in the relationship between leader humility and IWB. Moreover, we add job insecurity as a boundary condition to provide new insights into explaining IWB